Implementation of Local Network Access Restriction security on L2TP VPN with Firewall Filter Method - Tommi Alfian Armawan Sandi; Firmansyah; Eka Kusuma Pratama; Rian Septian Anwar (Jurnal Infortech, 2026)
The use of L2TP/IPSec-based Virtual Private Networks (VPNs) has become a common solution for providing remote access to local networks. However, VPN implementations without adequate access restrictions can potentially pose security risks, such as unauthorized access to internal resources, including shared directories on servers. This study aims to implement and analyze a local network access restriction strategy using a firewall filter with an accept-few-drop-any approach on an L2TP VPN network. The research method used is an experiment with the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) model approach. Testing was conducted in two scenarios: before and after the firewall filter implementation. The parameters analyzed included security aspects (access to shared directories) and network performance (latency, throughput, and packet loss). The results showed that before the firewall filter implementation, VPN users could access shared directories without restrictions. After the whitelisting strategy was implemented, access to file sharing services was effectively blocked, while other network services continued to run normally. In terms of performance, the firewall filter implementation did not have a significant impact on network performance.